Penerapan Prinsip Good Governance sebagai Upaya Menghindari Patologi Birokrasi Menuju Birokrasi yang Efisien - Sri Yulianty Mozin; Rahmatia Pakaya; Alfridho Musa; Haikal Supu; Sitti Warda Syarif; Siti Sabrina Kadir; Nafisya Datau; Meylis Rasid; Ralda Ivanka A. Labino (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
In the modern government administration system, bureaucracy plays a central role in running the wheels of government and public services, but it often faces bureaucratic pathologies that hinder performance and reduce public trust. This research aims to examine how the principles of good governance are implemented to prevent various issues that often occur within the bureaucracy. The main focus is to identify the types of problems that frequently arise, assess how the principles of good governance are implemented in bureaucratic institutions, and examine the extent to which this affects the efficiency and quality of public services. The research method used is a qualitative approach with a literature study, which involves the analysis of literature related to bureaucratic pathology and good governance. The research results show that bureaucratic pathologies, such as corruption, collusion, and nepotism, as well as inefficiencies in public service, can be addressed through the application of good governance principles that emphasize transparency, accountability, public participation, and the rule of law. The discussion shows that bureaucratic reform needs to address changes in the mindset and values within the organization, while also utilizing information technology to make bureaucratic work more efficient. In conclusion, the consistent implementation of good governance can prevent bureaucratic pathologies and create an efficient, clean, and responsive bureaucracy to the needs of society, thereby increasing public trust in the government.